Unraveling Shulman's syndrome: A rare case of eosinophilic fasciitis in a pediatric patient with fascial abnormalities on MRI - Hadj Hsain Ihssan; Ezzaky Sara; Maslouhi Kaoutar; Lahlou Chailmae; Marrakchi Salma; Allali Nazik; Chat Latifa; El Haddah Siham (Radiology Case Reports)
We report the case of a 15-year-old girl who presented with a 2-month history of severe fatigue and rapidly worsening myalgia. Biological tests revealed hypereosinophilia and an inflammatory syndrome. MRI showed increased signal intensity in the superficial and deep aponeurotic layers on T2-weighted images, with moderate fascia enhancement after contrast administration. A muscle biopsy of the arm was performed, revealing an accumulation of eosinophils in the muscle aponeuroses. Eosinophilic fasciitis (EF) is a rare connective tissue disorder characterized by inflammation of the fascia, leading to skin thickening and limb pain. While it predominantly affects adults, pediatric cases are rare, making diagnosis challenging due to its overlap with other fibrotic diseases.